Tony Bennett an American classic - Bennett, Tony 1926-2023; Streisand, Barbra 1942-; Legend, John 1978-; lang, k. d. 1961-; Botti, Chris 1962-; Krall, Diana 1964-; Juanes 1972-; John, Elton 1947-; Bublé, Michael 1975-; Wonder, Stevie 1950-; Aguilera, Christina 1980- (Sony BMG Music Entertainment, 2006)
A variety show re-creating the seminal venues of Tony Bennett's career
Originally produced for television. - Bonus features: The trailer; The Tony Bennett Dancers' rehearsals - Featurettes: The making of; Shooting black and white film; Walking the stars through their paces; Production design from page to stage
Narrated by Billy Crystal, Catherine Zeta-Jones, Bruce Willis, John Travolta, Robert De Niro
Choreographers: John DeLuca ; Rob Marshall. - Director of photography: Dion Beebe. Editor: Wyatt Smith
Smile (with Barbra Streisand) -- Sing, you sinners (with John Legend) -- Because of you (with k.d. lang ; feat. Chris Botti) -- The best is yet to come (with Diana Krall) -- The shadow of your smile (with Juanes) -- Rags to riches (with Elton John) -- Just in time (with Michael Bublé) -- For once in my life (with Stevie Wonder) -- Steppin' out (with Christina Aguilera) -- I left my heart in San Francisco
Keywords: Bennett, Tony / 1926-; Bennett, Tony <1926->; Popular music; Variety shows (Television programs)